2018
DOI: 10.1080/16583655.2018.1549529
|View full text |Cite
|
Sign up to set email alerts
|

Transient Dean flow in an annulus: a semi-analytical approach

Abstract: The mathematical model of a fully developed laminar transient flow formation between the gaps of two horizontally stationary concentric tubes forming concentric annulus due to the impact of sudden application of azimuthal pressure gradient is analysed. Analytical and numerical solutions of the momentum equations are obtained by the aid of two-step process. The first step is by solving the governing partial differential equation analytically by using Laplace transform technique in the Laplace domain. Using Riem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…14- (17) are to be transformed in order to determine the velocity, skin frictions and vorticity in time domain. Due to the intricate nature of the closed-form solutions, a numerical inversing procedure known as Riemann-Sum Approximation (RSA) employed by Jha and Odengle [20], Yusuf and Gambo [21], and Jha and Yahaya [22,23] which is remarkable for its precision has been utilized in transforming Eq. (14)- (17) to time domain as follows:…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…14- (17) are to be transformed in order to determine the velocity, skin frictions and vorticity in time domain. Due to the intricate nature of the closed-form solutions, a numerical inversing procedure known as Riemann-Sum Approximation (RSA) employed by Jha and Odengle [20], Yusuf and Gambo [21], and Jha and Yahaya [22,23] which is remarkable for its precision has been utilized in transforming Eq. (14)- (17) to time domain as follows:…”
Section: Methodsmentioning
confidence: 99%
“…In their work, they utilized a numerical inversing technique known as Riemann-Sum Approximation approach (RSA) in transforming the Laplace domain solution to time domain and concluded that velocity of the fluid is an increasing function of time. Other related literatures that adopted this method of solution include the work of Jha and Odengle [20], Yusuf and Gambo [21], and Jha and Yahaya [22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations